An alternative method to measure electrical conductivity (EC) and sodium adsorption ratio (SAR) in salt-affected soil extracts - Álvarez Torres, Beverly; Sotomayor Ramírez, David R.; Castro Chacón, José Pablo; Martínez Rodríguez, Gustavo; Pérez Alegría, Luis R.; DeSutter, Thomas M. (Frontiers in Environmental Science, 2023)
Soil degradation due to salts affects over 100 countries, especially in arid and semi-arid regions where salts migrate to the plant root zone via capillary action when evapotranspiration exceeds rainfall. Soil salinity reduces germination, growth, and root development, impacting crop yields, while excess sodium decreases water movement into the soil. Soil properties, namely electrical conductivity (ECe), sodium adsorption ratio (SARe), and pH (pHe), affected by sparingly and soluble salts, are typically analyzed using soil saturated paste (SP). However, a simpler and cost-effective alternative is assessing soil salinity using soil:water solutions at ratio 1:5 (SW). This study developed empirical models between EC1:5-ECe, SAR1:5-SARe, and pH1:5-pHe to monitor soil salinity and sodicity in Lajas Valley, Puerto Rico, an agricultural reserve with 1,140 mm of mean annual rainfall and soils classified as saline and/or sodic. The ECe Sampling, Assessment, and Prediction software for Response Surface Sampling Design (ESAP-RSSD) optimized soil sampling with 48 points. Measurements of EC, pH, cations (Ca 2+ , Mg 2+ , Na + ), and SAR were conducted using SP and 1:5 SW extracts. Simple linear regression models estimated ECe (R 2 > 0.93, p < 0.0001) and SARe (R 2 > 0.98, p < 0.0001) from 1:5 extracts. The pHe models varied with depth, showing a strong correlation (R 2 > 0.62, p < 0.0001) from 0 to 30 cm and weakening (R 2 > 0.27, p < 0.0022) from 90 to 120 cm. The simple linear regression models generally perform well for EC and pH variables, with better performance observed at shallower depths. SW proves to be a practical, cost-effective, and efficient method for assessing salt-affected soils in Lajas Valley. By enabling regular soil salinity analysis, the developed estimation models combined with SW extraction could improve soil management practices and agricultural productivity.